On the issue of the formation and development of legislation on the protection of lands of historical and cultural significance of the Republic of Kazakhstan: international and national aspects (Journal of actual problems of jurisprudence, 2018)
This article explores the development and development of legislation on the protection of historical and cultural heritage of Kazakhstan, including land and legal aspects. The author suggests ways to improve the existing legislation in the field of rational use and protection of historical and cultural sites in the Republic of Kazakhstan. Protection of historical and cultural objects, legal regulation of their exploitation, peculiarities of state regulation of these lands. At the same time, state programs aimed at preserving the historical heritage and their main directions are given. To preserve historical and cultural monuments, ways to improve and improve the legal status of their location are given.Key words: land, historical and cultural objects, historical and cultural purpose, land relations, historical and cultural experience, monuments.